1987
DOI: 10.1007/bf02449948
|View full text |Cite
|
Sign up to set email alerts
|

Geologic and atmospheric input factors affecting watershed chemistry in upper michigan

Abstract: ABSTRACT/The relationships between watershed variables and lakewater chemistry were examined for 53 lakes in the Upper Peninsula of Michigan to identify factors influencing lake sensitivity to atmospheric inputs. The lakes lie in three distinct geologic/geomorphic regions. Acid neutralization capacity (ANC), sulfate, and color were correlated with parameters related to atmospheric loading, watershed area and relief, hydrology, geology, and land use for the entire 53-lake set and for lower alkalinity subsets. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They concluded that bedrock geology was not an important determinant of water chemistry in their study due to the low weathering rates caused by the PREDICTING EURASIAN WATERMILFOIL PRESENCE Swedish climate. Other studies investigating lakes in the midwest and northeast United States (Newton et al 1987, Rapp et al 1987 have found bedrock and surficial geology to be important factors governing water chemistry, including alkalinity. Local groundwater inputs have also been found important in regulating milfoil growth and distribution (Lillie and Barko 1990).…”
Section: Importance Of Variablesmentioning
confidence: 99%
“…They concluded that bedrock geology was not an important determinant of water chemistry in their study due to the low weathering rates caused by the PREDICTING EURASIAN WATERMILFOIL PRESENCE Swedish climate. Other studies investigating lakes in the midwest and northeast United States (Newton et al 1987, Rapp et al 1987 have found bedrock and surficial geology to be important factors governing water chemistry, including alkalinity. Local groundwater inputs have also been found important in regulating milfoil growth and distribution (Lillie and Barko 1990).…”
Section: Importance Of Variablesmentioning
confidence: 99%
“…Other statistical analyses of large regional data sets have shown significant relationships between streamwater chemistry and some complex environmental factors, such as altitude and relief [24,32], catchment size [37], glacial influence [10,27], soil base saturation [5], land use [15] or some combination of these factors [11,12,19,21,22,31,34]. Surprisingly, the primary effect of precipitation amount was not often directly highlighted [16,36].…”
Section: Discussionmentioning
confidence: 99%